Validating policy prescription from benefit-cost assessments of mining through comparative analysis and test hypotheses - Boquiren, Arturo C. (The Philippine Review of Economics, 2008)
The paper proposes that benefit-cost analyses of mining be validated by comparative analyses and tests of hypotheses. Mining and non-mining communities can be compared to assess the contribution of mining to development. Further, tests of hypotheses can be used to determine whether mining communities are significantly different from non-mining communities in terms of poverty rates, health indicators, education, and other social indicators. Applying the said techniques in Benguet, Northern Philippines, the author found that mining communities, despite several years of mining operations, are not significantly different from non-mining communities.